From concepts to evaluation: mapping approaches to POCUS training assessment in low- and middle-income countries – a systematic scoping review - Eppel, Friedrich Leopold; Hunstig, Friederike; Kreuels, Benno; Bélard, Sabine (The Ultrasound Journal, 2026)
Background: Point-of-care ultrasound (POCUS) training programs are increasingly implemented in low- and middle-income countries (LMICs) to strengthen diagnostic capacity. Qualitative and sustainable implementation of POCUS capacity requires evaluation of training concepts and programs. In this review we collate approaches of how POCUS training programs and trainee competencies are evaluated in LMICs. Methods: This review presents a secondary analysis of data from a previous systematic scoping review that included 53 original studies on POCUS training in LMICs, identified through July 2023. Reported evaluation methods for POCUS training were extracted and categorized according to the Donabedian (structure - process - outcome) and Miller/De Biasio (levels of competence) frameworks. Data synthesis focused on the type, timing, and scope of evaluation across structural, procedural, and outcome domains. Results: POCUS training evaluation approaches were highly heterogeneous, with most studies using multiple methods. Pre- and post-course assessments predominated, focusing mainly on knowledge and technical skills. Competence evaluations covered all levels of the Miller/De Biasio framework, though most targeted lower-order levels, while workplace-based assessments were infrequent. When mapped to Donabedian’s model, outcome evaluations dominated, whereas structural and process assessments were inconsistently reported. Few studies demonstrated contextual adaptation, validity testing, or long-term evaluation of training outcomes. Conclusions: POCUS training evaluation in LMICs remains inconsistent and focuses primarily on short-term outcomes and basic competency levels. Applying Donabedian’s and Miller/De Biasio’s frameworks reveals critical evaluation deficiencies across system and learner dimensions and establishes a conceptional basis for more comprehensive and sustainable POCUS evaluation strategies.